Obstetric Outcomes of Referred Pregnancy Women for Delivery to Sakon Nakhon Hospital - Mungpooklang, Treewijit (Medical Journal of Sakon Nakhon Hospital, 2024)
The referral system is an important factor that helps pregnant women access to health services, especially in an emergency obstetric situation. Seamless and appropriateness of referral system is an important factor in the ultimate obstetric outcome. The aim of this study was to study the maternal and perinatal outcomes of referred pregnancy women to Sakon Nakhon hospital and factors relating to their obstetric outcomes. This was the retrospective descriptive study. The medical records of all obstetrics patients referred to Sakon Nakhon hospital for delivery from October, 2019 to September, 2020 were reviewed. Data were analyzed using the descriptive statistical and inferential statistics, Chi–square test and odd ratio. The statistically significant level of 0.05 was assigned. The results showed that the total numbers of 1,194 pregnancy women were referred to Sakon Nakhon hospital for delivery in the study period. Most cases (66.9%) were in the age range of 20–35 years. The most common diagnosis at the time of referral was cephalopelvic disproportion (21.1%). Anemia was the underlying disease in 20.6% of patients. About 43% and 45.7% of the patients delivered vaginally and by cesarean section, respectively. There was no maternal death in the referred cases. The supporting factors for birth asphyxia was prolong second stage (p = 0.016, odd ratio = 1.979 (95%CI, 1.128–3.473). The preventive factor for birth asphyxia was previous cesarean section (p = 0.028, odd ratio = 0.372 (95%CI, 0.149–0.930). The present study has shown that the maternal and perinatal morbidity and mortality was increased. Therefore, the development of skills and knowledge in emergency obstetrics care among healthcare providers and efficiency of referral system is essential to further reduce the fetomaternal morbidity and mortality.